A comparison of multiple sclerosis disease activity after discontinuation of fingolimod and placebo. Issue 3 (September 2017) - Vermersch, Patrick; Radue, Ernst-Wilhelm; Putzki, Norman; Ritter, Shannon; Merschhemke, Martin; Freedman, Mark S
Background: Cases of higher-than-expected disease activity have been reported following fingolimod discontinuation. Objective: The objective of this paper is to assess the risk of substantially higher-than-expected disease activity post-study drug discontinuation (SDD) at the individual patient level using data from the Phase III, placebo-controlled FREEDOMS and FREEDOMS II trials. Methods: Baseline gadolinium-enhancing T1-lesion volumes were used to statistically model the expected level of MRI disease activity post-SDD. Patients exceeding this level were classed as "MRI outliers." Patients with an unusually high increase in Expanded Disability Status Scale score, hospitalization for relapse, severe relapse, or relapse with incomplete recovery post-SDD were classed as "clinical outliers." Results: In FREEDOMS, the number of MRI outliers post-SDD was 2/69 (2.9%), 1/65 (1.5%) and 7/83 (8.4%) for the placebo, fingolimod 0.5 mg, and fingolimod 1.25 mg groups, respectively. In FREEDOMS II, the corresponding numbers were 4/72 (5.6%), 6/79 (7.6%) and 3/73 (4.1%). The number of clinical outliers across both trials was low. No consistent evidence of placebo vs fingolimod, dose-related or inter-trial patterns was discernable. Conclusion: The low number of clinical and MRI outliers and lack of any discernible pattern within and between trials, including between placebo and fingolimod, argues against a systematic risk of higher-than-expected recurrence of disease activity following discontinuation of fingolimod.